Superparamagnetni nanodelci in njihova uporaba v magnetni hipertermiji - Bužan Bobnar, Andreja (Matrika, 2018)
Hyperthermia is an important medical method for more efficient cancer treatment. Magnetic hyperthermia with nanoparticles enables localized heating of the treated tissue, which makes this method attractive. The method is based on heat generated by magnetic losses, due to Néel and Brown relaxation. The heating efficiency is defined by Specific Absorption Rate. With precisely selected strength and frequency of the magnetic field as well as the size of nanoparticles, very high tissue temperatures can be achieved (in certain cases even up to 60°C ). In addition to hyperthermia magnetic nanoparticles can be used also as a medium for drug delivery. Due to high standards in medicine magnetic hyperthermia with nanoparticles is not yet used in medical treatment.
Keywords: cancer treatment; magnetic hyperthermia; magnetic losses; magnetic nanoparticles; magnetna hipertermija; magnetne izgube; magnetni nanodelci; superparamagnetism; superparamagnetizem; zdravljenje raka